1999
DOI: 10.1053/euhj.1999.1282
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical outcome of cardiogenic shock during acute myocardial infarction among patients receiving reteplase or alteplase. Results from GUSTO-III

Abstract: Aims Reteplase has been reported to achieve better patency of the infarct artery than alteplase. As infarct artery patency is strongly associated with survival among patients with cardiogenic shock, we postulated that treatment with reteplase would improve outcomes among shock patients. MethodsWe compared 30-day mortality rates among patients in GUSTO-III who either presented with shock or developed shock after enrolment; all patients received either front-loaded alteplase or reteplase (two bolus doses of 10 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 29 publications
2
30
0
2
Order By: Relevance
“…These discouraging findings regarding the limitation of reperfusion therapy in cardiogenic shock patients are also supported by two of the most recent studies from GUSTO-III investigators [11]and Perez-Castellano et al [12]. Thus, it is possible that beyond a certain ‘therapeutic window’, revascularization is ineffective, possibly because of extensive metabolic insult or reperfusion injury to the myocardium.…”
Section: Discussionmentioning
confidence: 93%
“…These discouraging findings regarding the limitation of reperfusion therapy in cardiogenic shock patients are also supported by two of the most recent studies from GUSTO-III investigators [11]and Perez-Castellano et al [12]. Thus, it is possible that beyond a certain ‘therapeutic window’, revascularization is ineffective, possibly because of extensive metabolic insult or reperfusion injury to the myocardium.…”
Section: Discussionmentioning
confidence: 93%
“…[20][21][22] Elevated CRP concentration is associated with a poor prognosis in ACS. [23][24][25] We previously reported that a high CRP concentration is related to a poor prognosis in patients with AMI and poor long-term clinical outcomes after primary or rescue PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, primary PCI may be a better option in terms of survival than thrombolysis. [27][28][29] Finally, in the present study, treatment was initiated in a prehospital setting, which may not be feasible in all environments. Whether these results apply to in-hospital thrombolysis for patients treated early during the course of their symptoms is uncertain.…”
Section: Steg Et Al Prehospital Rtpa Vs Primary Pcimentioning
confidence: 99%